Worldwide Debate to Abolish the Death Penalty Forever - Ahmad, Masoud (2015)
Death penalty or capital punishment is a legal process whereby a person is put to death by the state as a punishment for a crime. The judicial decree that someone be punished in this manner is a death sentence, while the actual process of killing the person is an execution. Crimes that can result in a death penalty are known as capital crimes or capital offences. (Wikipedia, Capital Punishment)Capital punishment has, in the past, been practised by most societies. Currently 58 nations actively practise it, 97 countries have abolished it de jure for all crimes, 8 have abolished it for ordinary crimes only (maintain it for special circumstances such as war crimes), and 35 have abolished it de facto (have not used it for at least ten years and/or are under moratorium). Amnesty International considers most countries abolitionist, overall, the organisation considers 140 countries to be abolitionist in law or practice. (Amnesty, "Abolitionist and retentionist countries"). Keywords: Death penalty, worldwide debate